2017
DOI: 10.1534/g3.117.300125
|View full text |Cite
|
Sign up to set email alerts
|

Interchromosomal Transfer of Immune Regulation During Infection of Barley with the Powdery Mildew Pathogen

Abstract: Powdery mildew pathogens colonize over 9500 plant species, causing critical yield loss. The Ascomycete fungus, Blumeria graminis f. sp. hordei (Bgh), causes powdery mildew disease in barley (Hordeum vulgare L.). Successful infection begins with penetration of host epidermal cells, culminating in haustorial feeding structures, facilitating delivery of fungal effectors to the plant and exchange of nutrients from host to pathogen. We used expression Quantitative Trait Locus (eQTL) analysis to dissect the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 78 publications
2
12
0
Order By: Relevance
“…Additionally, as a proof of concept, we used Y2H-SCORES to identify and confirm the interaction of the barley powdery mildew effector, AVRA13, with the barley vesicle-mediated thylakoid membrane biogenesis protein, HvTHF1. This interaction, accompanied with previous evidence (21) and expression quantitative trait loci (eQTL) associations (22), support the involvement of HvTHF1 with resistance to powdery mildew.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Additionally, as a proof of concept, we used Y2H-SCORES to identify and confirm the interaction of the barley powdery mildew effector, AVRA13, with the barley vesicle-mediated thylakoid membrane biogenesis protein, HvTHF1. This interaction, accompanied with previous evidence (21) and expression quantitative trait loci (eQTL) associations (22), support the involvement of HvTHF1 with resistance to powdery mildew.…”
Section: Introductionsupporting
confidence: 74%
“…In addition, THF1 also has been found to destabilize several NB-LRR-type resistance proteins by binding their I2-like coiled-coil (CC) domains (41). Previous eQTL analysis performed by our group, combined with an interlogs search, revealed significant associations of Thf1 and its primary interactors with the Mla1 and MlLa trans-eQTL (22). These trans-eQTL associations ( Fig 4C) were observed at different powdery mildew infection stages, MlLa at penetration, and Mla1 during haustorial development.…”
Section: Experimental Validation Of Y2h-scores Identifies a New Intermentioning
confidence: 95%
See 1 more Smart Citation
“…Different processes associated with the targets included signaling, transcriptional regulation, and intracellular trafficking. In addition, when we integrated these results with previous expression quantitative trait locus (eQTL) analysis [39], we found that several MLA6 targets and/or secondary interactors associate significantly with the Mla1 (mildew resistance locus a1) and…”
Section: Y2h-scores Discards Auto-active Preys and Identifies Novel Interactors Of The Mla6 Barley Powdery Mildew Resistance Proteinmentioning
confidence: 87%
“…Rows followed by an asterisk ( � ) designate protein MlLa (Laevigatum resistance locus) trans-eQTL. These trans-eQTL associations occur at different powdery mildew infection stages, MlLa at fungal penetration and Mla1 during haustorial development (Table B in S9 Data) [39], and may provide clues as to the temporal control of these interactors in the immune response of barley to powdery mildew.…”
Section: Fig 6 Experimental Validation Of the Interaction Between The Mla6 Nlr Receptor And Barley Targetsmentioning
confidence: 99%